GOLDEN 2-LIKE Transcription Factors of Plants - Chen, Min; Ji, Meiling; Wen, Binbin; Liu, Li; Li, Shaoxuan; Chen, Xiude; Gao, Dongsheng; Li, Ling (Frontiers in Plant Science, 2016)
Golden2-like (GLK) transcription factors are members of the GARP family of Myb transcription factors with an established relationship to chloroplast development in the plant kingdom. In the last century, Golden2 was proposed as a second golden producing factor and identified as controlling cellular differentiation in maize leaves. Then, GLKs were also found to play roles in disease defense and their function is conserved in regulating chloroplast development. Recently, research on GLKs has rapidly increased and shown that GLKs control chloroplast development in green and non-green tissues. Moreover, links between phytohormones and GLKs were verified. In this mini-review, we summarize the history, conservation, function, potential targets and degradation of GLKs.